New psychosocial intervention approaches: reflections on the scope and limitations of the work of “psychosocial pairs” in secondary schools in Temuco, Chile (Revista Innova Educación, 2021)
The objective of this study was to analyze, in an exploratory manner and through a case study, to what extent the presence of psychosocial teams generates an expected positive impact on social relations within schools, and in turn, what may be the unexpected negative consequences that arise as a result of their implementation. The research was qualitative in approach and involved the participation of 22 people, with a total of 29 interviews. The results indicate, on the positive side, a progressive opening of schools to interdisciplinarity and intersectorial work in social intervention with students and their families. On the negative side, it was identified that the subject of regulation par excellence of these teams tends to be represented in the so-called "problematic student", in addition to the excess of administrative responsibilities to professionals, and, finally, an excessive confidence of the State in the "expert" knowledge, paradigmatically represented in the disciplines that make up these teams.
Keywords: Psychosocial pairs; school; problem student; public policy